La falsa identificazione del Santolinenone, componente fondamentale dell’olio essenziale di Santolina camaecyparissus - D’Auria, Maurizio (Chimica nella Scuola, 2024)
Luigi Francesconi published several articles on the identification of the main components of Santolina chamaecyparissus L. essential oil. He identified three ketones into the essence, giving the structure of santolinenone α and β. These compounds do not exist, and the erroneous identification derives from a wrong interpretation of the experimental available data as well as from the fact that he did not carry out decisive experiments for the identification of the structure.